Resolution of financial distress : an international perspective on the design of bankruptcy laws - Claessens, Stijn; Djankov, Simeon; Mody, Ashoka (Washington, D.C. : World Bank, 2001)
The book clearly illustrates the possibilities and methods of beneficial legal reform of bankruptcy procedures, as well as the pitfalls of misguided political action.
Thailand 282 -- Indonesia 292 -- Conclusion 301 -- References 302 -- 12. The Role of Cross-Border Mergers and Acquisitions in -- Asian Restructuring 305 -- Ashoka Mody and Shoko Negishi, World Bank -- Cross-Border M&A: Trends, Motives, and Impacts 306 -- East Asian Financial Distress and Recovery 314 -- Cross-Border M&As in East Asian Restructuring 321 -- Policy Implications 331 -- Conclusion 335 -- References 337 -- 13. Asset Management Companies 341 -- Daniela Klingebiel, World Bank -- The Centralized Versus the Decentralized Approach 342 -- The Different Types of Asset Management Companies 346 -- Evidence 349 -- Lessons from Cross-Country Experience 355 -- Appendix 13.A. Main Characteristics of Asset Management -- Companies 361 -- Bibliography and Reference List 372 -- Index 381.
Includes bibliographical references and index.
rua 15/04/15
Loans
Keywords: Bankruptcy; Debtor and creditor